2023
DOI: 10.53377/lq.13269
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Backbone of Library and Information Science: A Quest

Bijan Kumar Roy,
Parthasarathi Mukhopadhyay

Abstract: This study primarily aims to identify unique theories and specific uses of theories in the library and information science (LIS) domain. It provides a comprehensive list of the theories used in LIS journal articles indexed by Scopus (an abstract and citation database) from 1970–2021. It expands on the most common theories and highlights the areas and purposes for which used theories in the LIS domain. Our goal is to demonstrate the usages and applications of various borrowed theories from complementary discipl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 109 publications
0
3
0
Order By: Relevance
“…Nonetheless, of all utilized theories, TAM and UTAUT were found to be the most frequently utilized ones. Previous LIS studies (Roy & Mukhopadhyay, 2023;Ukwoma & Ngulube, 2021) have also confirmed the extensive use of these theories in most LIS research. In terms of research methodology, the findings indicate that a significant proportion of the analyzed articles did not specify the research design employed.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…Nonetheless, of all utilized theories, TAM and UTAUT were found to be the most frequently utilized ones. Previous LIS studies (Roy & Mukhopadhyay, 2023;Ukwoma & Ngulube, 2021) have also confirmed the extensive use of these theories in most LIS research. In terms of research methodology, the findings indicate that a significant proportion of the analyzed articles did not specify the research design employed.…”
Section: Discussionmentioning
confidence: 56%
“…In fact, the significance of theory is underscored by certain journals (e.g., Wiley), which exhibit a preference for articles that offer substantial theoretical contributions (Díaz Andrade et al, 2023). Although scholars have recognized the importance of applying theories in research, it is undeniable that there is a scarcity of explicit theories in the field of LIS as evidence from research (Hjørland, 2000;Lor, 2014;Roy & Mukhopadhyay, 2023) indicates. As a result, often theories from other disciplines such as psychology, sociology, or management are applied.…”
Section: Related Literaturementioning
confidence: 99%
See 1 more Smart Citation